Blood-based candidate biomarkers of the presence of neuropsychiatric systemic lupus erythematosus in children. Issue 1 (5th November 2014) - Brunner, Hermine I; Klein-Gitelman, Marisa S; Zelko, Frank; Beebe, Dean W; Foell, Dirk; Lee, Jiha; Zaal, Ahmad; Jones, Jordan; Roebuck-Spencer, Tresa; Ying, Jun
Abstract : Objective: To examine select brain-reactive proteins for their usefulness to serve as blood-based biomarkers in the screening for neurocognitive deficits in childhood-onset systemic lupus erythematosus (cSLE-NCD). Methods: Patients withcSLE (n=40) were studied longitudinally (month 1; month 18): working memory, psychomotor speed and visuoconstructional ability were assessed using formal neurocognitive testing to determine the presence of cSLE-NCD. Patients also completed the computerised Paediatric Automated Neuropsychological Assessment Metrics. The following brain-reactive proteins were measured in the blood: neutrophil gelatinase associated lipocalin (NGAL), S100B, S100A8/9, antibodies to NR2 glutamate receptor (aNR2-AB), ribosomal-P (aP-AB), glycoprotein-1 (aGP1-AB), and lupus anticoagulant. Results: cSLE-NCD was present in 6 of 40 patients at baseline and 4 of 27 patients with 18-month information. aP-AB positivity was more commonly present with cSLE-NCD than without (p=0.05). aP-ABs were negatively associated with performance on tests assessing working memory, psychomotor speed and visuoconstructional ability in using formal neurocognitive testing. There were also significant negative associations between aP-AB, S100A8/9, aNR2-AB, aGP1-AB, and lupus anticoagulant and accuracy rates on select Paediatric Automated Neuropsychological Assessment Metrics subtests (p<0.05). Over time, decline in cognitive performance was more pronounced among patients with higher NGAL and aNR2-AB levels. Combinations of serum levels of S100A8/9, S100B, NGAL, aNR2-AB and aP-AB were able to identify cSLE-NCD (sensitivity: 100%; specificity 76%) in exploratory analysis. Conclusions: Select brain-reactive proteins in the blood are associated with cognitive performance and the presence of cSLE-NCD, cross-sectionally and over time. This raises the possibility that testing of these proteins may assist with the screening of cSLE-NCD.